Exosomes derived from umbilical cord mesenchymal stem cells carryingmiR-296-3p improve symptoms of rat model with gestational diabetes mellitus - ZHAO Dan, LIU Tingxiang, ZHENG Chuwen, HE Wencong (Jichu yixue yu linchuang)
Objective To investigate the improvement of exosomes (Exo) derived from umbilical cord mesenchymal stem cells (MSCs) carrying miR-296-3p on blood lipid metabolism and immune function in gestational diabetes mellitus rats. Methods After transfection of MSCs with miR-296-3p-NC and miR-296-3p mimics, Exo was extracted to obtain MSCs-Exo-miR-NC and MSCs-Exo-miR-296-3p, respectively. RT-qPCR was used to detect the expressionof miR-296-3p; Pregnant mice were prepared and induced to establish a GDM model by tail vein injection of streptozotocin. Then they were randomly grouped into a model group, MSCs-Exo-miR-NC group, and MSCs-Exo-miR-296-3p group with 10 each. In addition, 10 pregnant mice were prepared as the control group. The weight of mother and fetal mice, four items of blood lipids and immune organ index in each group were measured after intervention with MSCs-Exo-miR-NC and MSCs-Exo-miR-296-3p. ELISA was applied to measure the level of serum immunoglobulin and immune inflammatory factors. Flow cytometry technology was applied to detect the immune function of peripheral blood T lymphocytes of rats in various groups, and their CD4+ and CD8+ values were compared. Results Compared with the control group, the maternal rat weight and fetal rat weight, serum triglycerides (TG), total cholesterol (TC), low-density lipoprotein (LDL-C), IL-6 and IL-8 levels and CD8+ ratio of rats in model group increased (P＜0.05), the spleen and thymus index, serum high-density lipoprotein (HDL-C), IgA, IgG, IgM, IL-2 and IL-10 levels and CD4+ ratio decreased (P＜0.05). Compared with the model group, the maternal rat weight and fetal rat weight, serum TG, TC, LDL-C, IL-6 and IL-8 level, and CD8+ ratio of rats from MSCs-Exo-miR-NC group and MSCs-Exo-miR-296-3p group decreased (P＜0.05), the spleen and thymus index, serum HDL-C, IgA, IgG, IgM, IL-2 and IL-10 levels and CD4+ ratio all increased (P＜0.05); MSCs-Exo-miR-296-3p had a stronger effect on various indicators of GDM rats (P＜0.05). Conclusions Exo derived from MSCs carrying miR-296-3p improves blood lipid metabolism and immune function of GDM rats.